E-management for school resource centre - Muhammad Ashraf, Kamarudin (2018)
The purpose of this paper is to change or upgrade the current manual system into a computerized system to achieve faster and efficient in processing information, automatic generation of many types of reports , larger reductions in cost of hardware and software and have a more timely information produced. Books in school resource center are often lost as no proper managing procedure is implemented. School Teachers also have troubles finding out what book is in the resource center’s possession. Student’s who borrowed the books often not returned the borrowed books but remained unnoticed by the management of school resource center because checking and trying to find out what books is there and is missing is a tedious task without a proper management system and take a long time. The student also leave the school unpunished as the record of him borrowing the book can easily be lost or destroyed with no trace. To solve the problems at hand, system requirements and other related data from the school resource center is then gathered and analyzed to create a first defined system requirements. Then existing system that tackles the problems with their own ways is find, analyze and compare. Their strength, weakness and the requirements they are lacking is find and then begin to construct the new system design that fulfilled all requirements. The project use Rapid Application Development methodology from the beginning until the end to make sure the project can be delivered on time within the project’s budget and is of high quality. The final system produced then be able to tracks the whereabouts of any books within seconds and able to produce accurate reports based on the information recorded. To conclude, the computerized system manage to solve all problems that the current manual system is facing with an addition of several improvement to ease the tedious task of managing the school resource center.